PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN HOTEL PURI INDAH MATARAM - Febdilan, Firman Koma (JAB (Jurnal Akuntansi & Bisnis), 2017)
This study aimed to describe leadership, motivation, and employee performance, analyze the influence of leadership and motivation on employee performance, and to analyze the leadership and motivation among the dominant influence on employee performance. This research included in the category explanatory research. Samples many as 52 people. The analysis technique used is multiple regression analysis, F test and t test. Based on the descriptive results show that leadership run has been able to carry out the role of transformational leaders. Employee motivation Puri Indah Hotel Mataram is already very high, and is influenced by need for achievement, need for power, and need for affiliation. Employee performance is predominantly influenced by transformational leadership compared with motivation. Transformational leadership is essentially emphasizes a leader needs to motivate subordinates to carry out responsibilities of employees over the employees expect. Motivation is essential in improving the effectiveness of a work, because employees who have high motivation will strive with all his strength so that work can be managed as well as possible. If the employee's personal needs are met, then the employees will be able to work harder and can improve employee performance.Â Keywords: transformational leadership, motivation, employee performance